Penggunaan Media Puzzle Angka untuk Meningkatkan Sosial Emosional Anak Tunarungu Usia 8 Tahun - Nurhasikin; Mufidah, Nurul; Lestari, Tri Ayu (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study was to determine the social emotional development of children through number puzzle games, to determine the response of children during the learning process using number puzzle games. This research is a Classroom Action Research namely observing the activities that are deliberately raised that occur in a class. The action is given by the teacher or with the direction the teacher gets from the research. This classroom action research was carried out collaboratively where this research was carried out in collaboration between researchers and teachers in one class. The main subjects in this study were children aged 8 years.